2019
DOI: 10.1590/1806-93042019000400006
|View full text |Cite
|
Sign up to set email alerts
|

Abortion among women living with or not living with HIV/AIDS users of public health services in São Paulo municipality: prevalence, contexts and reasons

Abstract: Objectives: we investigated the lifetime prevalence of abortion and life contexts and reasons reported for first abortion among women living (WLHA) and not living with HIV/AIDS (WNLHA).Methods: representative samples of 975 users of public health care reference network for HIV/AIDS and of 1,003 users of the primary care public services in São Paulo municipality were selected by cluster-stratified sampling and answered an electronic socio-behavioral questionnaire.Results: the prevalence of abortion was 11.9% (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…sexual partnerships, having had children prior to the index pregnancy, and living with a sexual partner during pregnancy were identified as factors associated with the high prevalence of induced abortion among women living with HIV [23,24].…”
Section: Plain Language Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…sexual partnerships, having had children prior to the index pregnancy, and living with a sexual partner during pregnancy were identified as factors associated with the high prevalence of induced abortion among women living with HIV [23,24].…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Existing studies, however, appear to suggest that the prevalence of induced abortion is higher among women living with HIV compared to HIV-negative women [ 10 , 23 ]. For instance, Pinho et al [ 24 ] found that the prevalence of induced abortion was 11.9% among women living with HIV/AIDS and 3.0% among women not living with HIV/AIDS. Another study also found that the prevalence of induced abortion among women living with HIV/AIDS was 6.5%, while women not living with HIV/AIDS was 2.9% [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation